+0  
 
0
62
1
avatar

The question says: Solve for df where V = df - di

                                                                     tf - ti

 

I am really stuck on this and I was hoping someone could help me out. 

Thank you!

 Jan 7, 2021

Best Answer 

 #1
avatar
+1

V = df - di/( tf - ti)        multiply both sides by (tf-ti)

 

V ( tf - ti)   = df -di

V (tf-ti) + di = df

 Jan 7, 2021
 #1
avatar
+1
Best Answer

V = df - di/( tf - ti)        multiply both sides by (tf-ti)

 

V ( tf - ti)   = df -di

V (tf-ti) + di = df

Guest Jan 7, 2021

22 Online Users

avatar
avatar